Plastid methylerythritol phosphate pathway participates in the hypersensitive response-related cell death in Nicotiana benthamiana - Lee, Sanghun; Jo, Sung Hee; Hong, Chi Eun; Lee, Jiyoung; Cha, Byeongjin; Park, Jeong Mee (Frontiers in Plant Science, 2022)
Programmed cell death (PCD), a characteristic feature of hypersensitive response (HR) in plants, is an important cellular process often associated with the defense response against pathogens. Here, we studied the involvement of LytB, a gene encoding 4-hydroxy-3-methylbut-2-enyl diphosphate reductase that participates in the final step of the plastid methylerythritol phosphate (MEP) pathway, in plant HR cell death. In Nicotiana benthmiana plants, silencing of the NbLytB gene using virus-induced gene silencing (VIGS) caused plant growth retardation and albino leaves with severely malformed chloroplasts. In NbLytB-silenced plants, HR-related cell death mediated by the expression of either the human proapoptotic protein gene Bax or an R gene with its cognate Avr effector gene was inhibited, whereas that induced by the nonhost pathogen Pseudomonas syringae pv. syringae 61 was enhanced. To dissect the isoprenoid pathway and avoid the pleiotropic effects of VIGS, we used chemical inhibitors that specifically inhibit isoprenoid biosynthesis in plants. Treatment of N. benthamiana plants with fosmidomycin, a specific inhibitor of the plastid MEP pathway, effectively inhibited HR-related PCD, whereas treatment with mevinolin (cytoplasmic mevalonate pathway inhibitor) and fluridone (carotenoid biosynthesis inhibitor) did not. Together, our results suggest that the MEP pathway as well as reactive oxygen species (ROS) generation in the chloroplast play an important role in HR-related PCD, which is not displaced by the cytosolic isoprenoid biosynthesis pathway.